2021
DOI: 10.1093/ijnp/pyab050
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Seltorexant as Adjunctive Therapy in Major Depressive Disorder: A Phase 2b, Randomized, Placebo-Controlled, Adaptive Dose-Finding Study

Abstract: Background Seltorexant, a selective antagonist of human orexin-2 receptors, demonstrated antidepressant effects in a previous exploratory study in patients with major depressive disorder (MDD). Methods To replicate and extend this observation, a double-blind, adaptive dose-finding study was performed in patients with MDD who had an inadequate response to 1-3 selective serotonin/serotonin-norepinephrine reuptake inhibitors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
(43 reference statements)
0
27
0
Order By: Relevance
“…Seltorexant is being investigated in patients with MDD and co‐morbid insomnia [102, 103], in which it improved sleep and depressive symptoms over 28 days of dosing and enhanced NREM delta power, a feature not replicated by other hypnotics [103]. A Phase IIb study (NCT03227224) reported clinically relevant reductions in depressive symptoms in MDD patients with suboptimal responses to antidepressants with adjunct seltorexant, and more so, in patients with sleep disturbances [104]. Further clinical studies are ongoing as posted in clinicaltrials.gov (NCT04532749, NCT04533529).…”
Section: Drug Discovery and Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Seltorexant is being investigated in patients with MDD and co‐morbid insomnia [102, 103], in which it improved sleep and depressive symptoms over 28 days of dosing and enhanced NREM delta power, a feature not replicated by other hypnotics [103]. A Phase IIb study (NCT03227224) reported clinically relevant reductions in depressive symptoms in MDD patients with suboptimal responses to antidepressants with adjunct seltorexant, and more so, in patients with sleep disturbances [104]. Further clinical studies are ongoing as posted in clinicaltrials.gov (NCT04532749, NCT04533529).…”
Section: Drug Discovery and Developmentmentioning
confidence: 99%
“…A Phase IIb study (NCT03227224) reported clinically relevant reductions in depressive symptoms in MDD patients with suboptimal responses to antidepressants with adjunct seltorexant, and more so, in patients with sleep disturbances [104].…”
Section: Hcrt-r2 Agonistsmentioning
confidence: 99%
“…In a phase IIb, randomized, placebo-controlled, adaptive dose-finding study, 287 patients with MDD who had an insufficient response to 1-3 SSRI/SNRI during the current episode were randomized to placebo or seltorexant (20 or 40 mg) as add-ons to the currently administered antidepressant ( Savitz et al, 2021 ). A significant reduction in depressive symptoms (MADRS scores) was observed for seltorexant (20 mg), and in the subset of patients with sleep disturbance, the difference between seltorexant 20 mg and placebo was larger ( Savitz et al, 2021 ).…”
Section: Orexin Receptors Antagonistsmentioning
confidence: 99%
“…TEAE, treatment-emergent adverse events; AE, adverse events; SAE, severe adverse events; EPS, extrapyramidal symptoms. Based on the data from Mi et al, 2021 ; Ball et al, 2015 ; Carhart-Harris et al, 2016 ; COMPASS, 2021 ; Citrome, 2019 ; Fava et al, 2018 ; Durgam et al, 2016 ; Fava et al, 2019 ; Loebel et al, 2022 ; Savitz et al, 2021 ; Kanes S. et al, 2017 ; Gunduz-Bruce et al, 2019 ; Deligiannidis et al, 2021 ; Dichtel et al, 2020 ; Tyring et al, 2006 ; Langley et al, 2010 ; Raison et al, 2013 ; Abbasi et al, 2012 .…”
Section: Anti-inflammatory Therapies As Potential Treatments For Depr...mentioning
confidence: 99%
“…For example, in trials with DORAs/SO2RAs for insomnia and depression (55,56) the drugs were administered at bedtime, and in a trial with SO1RA for binge eating disorder the drug was given during morning and evening meals (NCT04753164) (57). In the context of the possible use of OXR antagonists for the treatment of NPS in PwD, bedtime administration has the advantages of maximizing the drug's efficacy on nighttime problems and reducing the risk of daytime somnolence; however, little effect may be expected on disturbances that mostly manifest during the day [except those instances where amelioration of daytime symptoms is achieved through improved nighttime problems, as in the case of depression (56)]. Conversely, daytime dosing may have a greater impact on symptoms, which are expressed during the day, but (depending on the dose) it may be associated with a higher risk of somnolence.…”
Section: Predicted E Ects Of Pharmacological Orexin Receptor Modulati...mentioning
confidence: 99%